Empirical studies of the construction of discourse - Loureda Lamas, Óscar; Recio Fernández, Inés; Nadal, Laura; Cruz, Adriana (Pragmatics & beyond / New series, 2019)
Inhaltsverzeichnis: Introduction / Óscar Loureda, Inés Recio Fernández, Adriana Cruz and Laura Nadal -- Part I. Corpus-based studies: 1. Challenges in the contrastive study of discourse markers: the case of then / Karin Aijmer -- 2. Local vs. global scope of discourse markers: Corpus-based evidence from syntax and co-occurring pauses / Ludivine Crible -- 3. Prosodic versatility, hierarchical rank and pragmatic function in conversational markers / Antonio Hidalgo Navarro and Diana Martínez Hernández -- 4. A preliminary typology of interactional figures based on a tool for visualizing conversational structure / Guadalupe Espinosa-Guerri and Amparo García-Ramón -- 5. Causal relations between discourse and grammar: Because in spoken French and Dutch / Liesbeth Degand -- 6. A corpus-based comparative study of concessive connectives in English, German and Spanish: The distribution of although, obwohl and aunque in the Europarl corpus / Volker Gast -- Part II. Experiment-based studies: 7. Processing patterns of focusing in Spanish / Adriana Cruz and Óscar Loureda -- 8. Expectation changes over time: How long it takes to process focus imposed by German sogar / Johannes Gerwien and Martha Rudka -- 9. Processing implicit and explicit causality in Spanish / Laura Nadal and Inés Recio Fernández -- Part III. Combined approaches: 10. Subjectivity and Causality in discourse and cognition: Evidence from corpus analyses, acquisition and processing / Ted J. M. Sanders and Jacqueline Evers-Vermeul -- 11. Causal connectives revisited: A corpus and experimental investigation of result discourse markers in English / Marta Andersson.
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Diskursanalyse